Salmonella-induced changes in the gut microbiota and immune response genes transcriptome during administration of vancomycin and Bacteroides fragilis - Yu. V. Bukina; A. M. Kamyshnyi; N. N. Polishchuk (Zaporozhye State Medical University, 2017)
The aim. To study Salmonella-induced changes in the intestinal wall microbiota, the expression of Salmonella effector proteins SipA, SopB, SopE2 and transcriptional activity of genes FFAR2, Foxp3, RORγt in rat GALT during administration of vancomycin and B.fragilis. Methods. Investigations of qualitative and quantitative composition of the microbiota of the wall of the small intestine were carried out, and the expression level of rat genes Foxp3, Rorc (Royt), FFAR2 and Salmonella effector proteins SipA, SopB and SopE2 were determined by RT-PCR, the relationship between groups of microorganisms was established. Results. Administration of B.fragilis against the background pre-treatment with vancomycin and Salmonella infection alters the quantitative composition of the microbiota in the wall of the small intestine contents: a decrease in Salmonella spp., E.coli, P.aeruginosa, Proteus spp., Enterobacter spp., Klebsiella spp. and Shigella spp., as well as increasing Bacteroides spp., E.faecalis, E.faecium and Peptostreptococcus anaerobius. The level of expression of Salmonella effector proteins in animals with the combined administration of vancomycin and S.enteritidis (I group), S.typhimurium (II group) increased: SopB - 101 and 20 times; SopE2 - 80 and 2 times; SipA - 613 times (II group), and also 5-fold decrease was noted in the I group. Relative normalized number of mRNA of genes FFAR2, Foxp3, RORγt in GALT of rats in groups III and IV increased: FFAR2 - 2.7 and 5.4 times; Foxp3 - 2.5 and 85 times, RORγt level decreased by 70% and only in IV group. Conclusions. Using B.fragilis creates conditions for the correction of Salmonella-induced changes of the intestinal microbiome. Pretreatment of animals with vancomycin causes increased transcriptional activity of genes SipA, SopB and SopE2, except SipA after administration of S.enteritidis. Administration of B.fragilis increases the level of mRNA of genes FFAR2 and Foxp3 in GALT and reduces RORγt after infection with S. typhimurium.